Pengaruh Disiplin Kerja Dan Kepuasan Kerja Terhadap Kinerja Karyawan PT OPQ - Orin Fernanda; Eka Mariyanti (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze the effect of work discipline and job satisfaction on employee performance at PT OPQ. The research background stems from a decline in performance in several work units, low team collaboration, high levels of tardiness, and low job satisfaction among employees. This study employs a quantitative method with a population of 112 employees, all of whom were taken as the sample using the total sampling technique. Data were collected through a four-point Likert scale questionnaire and analyzed using multiple linear regression after passing the classical assumption tests. The results indicate that work discipline has a positive and significant effect on employee performance, job satisfaction also has a positive and significant effect on employee performance, and simultaneously both variables have a positive and significant effect on employee performance. The coefficient of determination shows that work discipline and job satisfaction contribute substantially to the variation in employee performance, while the remaining variation is influenced by other factors outside the research model. These findings emphasize that improving work discipline and job satisfaction is a strategic step in enhancing employee performance at PT OPQ.